Construction of self-dual binary [2²ⁿ,2²ⁿ⁻¹,2ⁿ]-codes - Hannusch, C.; Lakatos, P. (Algebra and Discrete Mathematics, 2016)
The binary Reed-Muller code RM(m−n,m) corresponds to the n-th power of the radical of GF(2)[G], where G is an elementary abelian group of order 2m. Self-dual RM-codes (i.e. some powers of the radical of the previously mentioned group algebra) exist only for odd m. The group algebra approach enables us to find a self-dual code for even m=2n in the radical of the previously mentioned group algebra with similarly good parameters as the self-dual RM codes.